Past the Pandemic: a virtual intervention supporting the well-being of healthcare workers through the COVID-19 pandemic - Millar, Amanda M.; Doria, Amanda M.; Choi, Leslie M.; McGladrey, Laura; Duffy, Korrina A.; Berkowitz, Steven J. (Frontiers in Psychology, 2023)
To decrease burnout and improve mental health and resiliency among doctors, nurses, and hospital staff during the COVID-19 pandemic, the University of Colorado partnered with ECHO Colorado to offer the state’s healthcare workforce an interactive, psychoeducational, and online intervention that encouraged connection and support. The series utilized the Stress Continuum Model as its underlying conceptual framework. Between July 2020 and February 2022, 495 healthcare workers in Colorado participated in the series across eight cohorts. One-way repeated measures ANOVAs were performed to test for differences in pretest and posttest scores on series’ objectives. Healthcare workers showed significant improvement from pretest to posttest in (1) knowing when and how to obtain mental health resources, F(1, 111) = 46.497, p < 0.001, (2) recognizing of the importance of being socially connected in managing COVID-related stress, F(1, 123) = 111.159, p < 0.001, (3) managing worries, F(1, 123) = 94.941, p < 0.001, (4) feeling prepared to manage stressors related to the pandemic, F(1, 111) = 100.275, p < 0.001, (5) feeling capable in dealing with challenges that occur daily, F(1, 111) = 87.928, p < 0.001, and (6) understanding the Stress Continuum Model F(1, 123) = 271.049, p < 0.001. This virtual series showed efficacy in improving the well-being of healthcare workers during a pandemic and could serve as a model for mental health support for healthcare workers in other emergency response scenarios.